DYNAMICS OF MICROECOLOGICAL INDICATORS OF SEXUAL WAYS IN PREGNANT INFECTIONS WITH INFLAMMATORY DISEASES OF REPRODUCTIVE SYSTEM - Lisyana, T.O.; Ponomaryova, I.G.; Katsalap, O.M.; Dobrochinska, L.I. (World of Medicine and Biology, 2018)
In pregnant women with inflammatory diseases of the genital tract, pathological microbiocenosis forms with a change in the ratio of obligate and optional parts of resident microflora. The work assesses the structure of bacterial associations and studied the dynamics of changes between aerobic and anaerobic components of the genital tract microbiocenosis in 98 pregnant women with inflammatory diseases of the reproductive system in different periods of pregnancy. The data obtained indicate that the microbiocenosis of the genital tract in women with inflammatory diseases at different stages of pregnancy is characterized by the formation of bacterial complexes and differs in the frequency of pathological manifestations (anaerobic vaginosis, aerobic vaginitis, candidiasis). An analysis of the microecology of the vagina of pregnant women with inflammatory diseases of the genital tract shows that in 33.3% of women in the first trimester of pregnancy the biocenosis is characterized by associative forms of bacterial and fungal contamination of the vaginal mucosa. The composition of associations with the greatest frequency included representatives of the aerobic conditionally pathogenic microflora. Among the Gram-positive cocci were registered: S. faecalis - 19.4%, S. agalactiae - 13.9%, S. epidermidis (rem + and hem-) - 13.9% and 19.4%. In the composition of bacterial flora associations, enterobacteria had a significant presence: E. coli with unchanged properties (22.2%) and Klebsiella pn. (13.9%). Among the anaerobic microflora, Bacteroides melaninogenicus (22.2%), Fusobacterium nucleatum (16.7%), Peptostreptococcus anaerobius (25%) prevailed among women in the first trimester of pregnancy. Eubacterium spp. Was hanging at a lower frequency. and Propionibacteriium spp. The frequency of registration of fungi of the genus Candida in the association of pregnant women during the primary examination was 27.8%. In 44.4% of women the quantitative indices of sowing protective microflora were reduced. In women in the second trimester of pregnancy, there is an increase in the frequency and quantitative indices of dissemination of the genital tract, both aerobic and anaerobic microflora. As the pregnancy period increased, the presence of anaerobes increased in the spectrum of the microflora released from the vagina: Peptostreptococcus anaerobius (34.4%), Bacteroides melaninogenicus (28.1%), Fusobacterium nucleatum (21.9%), Eubacterium lentum (18.8%). Among the representatives of facultative aerobic microflora, an increase in the frequency of detection of E. coli haem- (25%), E. coli heme + (18.8%), S. faecalis (21.9%), S. agalactiae (15.6%). Substantially increased rates of sowing mushrooms p. Candida. In the third trimester of pregnancy, a tendency towards a decrease in the level of transient facultative aerobic microflora was observed in women in the structure of microbial associations (E. coli heme, E. coli heme +, Klebsiella spp., S. faecalis, S. epidermidis heme + and S. epidermidis heme ). But, the concentration of these microorganisms exceeded the diagnostic level (> lg 3.5 CFU / ml). The frequency of vaginal contamination by anaerobes tended to increase - Peptostreptococcus spp. - 40%, Bacteroides spp. - 33.3%, Fusobacterium spp. - 26.7%, Eubacterium spp. - 23.3%. It should also be noted the positive dynamics to restore the level of protective microflora - lactobacilli. In 46.7% of the women surveyed in the third trimester of pregnancy, their registration rates were normal, others tended to normalize.